Upaya Mencegah Tindak Kriminal pada Lingkungan Tempat Tinggal dengan Pemasangan CCTVdi Desa Selayang - Ramdani Safitri, Habibi; Aminuddin, Harris; Adwin Adam , Hikmah; Lase, Yuyun Yusnida (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2024)
A peaceful, safe, and comfortable living environment is a dream for people who want to settle in an area. Interactive socialization between residents based on equality and high social morals is a condition for achieving harmony and happiness. However, the insecurity that comes from theft, loss, and other activities felt by the community has led to unrest. This activity is the basis for joint activities with the Village Community in Selayang, Deli Serdang Regency, to carry out village security through the Selayang Village Cooperation with the Medan State Polytechnic Service Team through the means of village monitoring technology (PANDES) by utilizing CCTV. The existence of location monitoring technology that can detect moving objects in the village monitoring area is used to access the community that inhabits the former oil palm plantation area. PANDES is essential because the distance between residents' houses is relatively far, between 6-10 m; many vacant lots are overgrown with large trees and dense bushes. This condition makes crime opportunities quickly arise by utilizing the conditions of the community's residence. The existing problems are solved through community service activities by presenting PANDES through the provision of Closed Circuit Television (CCTV) monitors. CCTV is designed to detect moving objects within a radius of 20 meters.